ANALISIS PENDAPATAN USAHA â€œCAPTIKUSâ€ DI DESA WUWUK BARAT KECAMATAN TARERAN (Analysis of "Capticus" Businiss income in West Wuwuk Village, Tareran District) - Kansye V. Kellah; Grace A. J. Rumagit; Audrey J. M. Maweikere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to analyze the income received by â€œcaptikusâ€ business farmers in West Wuwuk Village, Tareran District, South Minahasa Regency, North Sulawesi Province. The research was conducted from October 2019 to August 2020. This research was a quantitative research. The data were collected by means of structured interviews using a questionnaire, to 6 â€œcaptikusâ€ producers who were selected intentionally (purposive sampling method) from 15 active â€œcaptikusâ€ producers in West Wuwuk Village. The data analysis method used in this research was income analysis by calculating the difference between revenue and the amount of costs used per week. The results showed that the average income received by captikus farmers in Wuwuk Barat Village Tareran District, South Minahasa Regency, North Sulawesi Province was IDR 992,934.14 per week.